Treatment of aortic valve endocarditis with stented or stentless valve - Clemence, Jeffrey (J Thorac Cardiovasc Surg, 2022)
OBJECTIVE: The study objective was to provide evidence for choosing a bioprosthesis in treating patients with active aortic valve endocarditis. METHODS: From 1998 to 2017, 265 patients with active aortic valve endocarditis underwent aortic valve replacement with a stented valve (n = 97, 37%) or a stentless valve (n = 168, 63%) with further breakdown into inclusion technique (n = 142, 85%) or total root replacement (n = 26, 15%). Data were obtained from the Society of Thoracic Surgeons database aided with chart review, surveys, and National Death Index data. RESULTS: The median age of patients was 53 years (43–56) in the stented group and 57 years (44–66) in the stentless group. The stented and stentless groups had high rates of heart failure (54% and 40%), liver disease (16% and 7.7%), prosthetic valve endocarditis (14% and 48%), root abscess (38% and 70%), and concomitant ascending aorta procedures (6.2% and 22%), respectively. The stentless group required permanent pacemakers in 11% of cases. Operative mortality was similar between groups (6.2% and 7.1%). The 5-year survival was 52% and 63% in the stented and stentless groups, respectively. Significant risk factors for long-term mortality included liver disease (hazard ratio, 2.38), previous myocardial infarction (hazard ratio, 1.64), congestive heart failure (hazard ratio, 1.63), and renal failure requiring dialysis (hazard ratio, 4.37). The 10-year cumulative incidence of reoperation was 12% and 3.4% for the stented and stentless groups, respectively. The 10-year freedom from reoccurrence of aortic valve endocarditis was 88% for the stented and 98% for the stentless groups. CONCLUSIONS: Both stented and stentless aortic valves are appropriate conduits for replacement of active aortic valve endocarditis for select patients.